Quanduzhong capsules for the treatment of grade 1 hypertension patients with low-to-moderate risk: A multicenter, randomized, double-blind, placebo-controlled clinical trial - Xu, Xuan; Tian, Wende; Duan, Wenhui; Pan, Chaoxin; Huang, Mingjian; Wang, Qinggao; Yang, Qinghua; Wen, Zhihao; Tang, Yu; Xiong, Yao; Zhu, Zhiyun; Liu, Yuanyuan; et al. (Frontiers in Pharmacology, 2023)
Background: Duzhong [DZ (Eucommia ulmoides Oliv.)] is regarded as a traditional Chinese medicine with a history dating back more than 2000 years. This herb is considered a nourishing herb in China and is commonly used as a tonic to strengthen muscles and bones, nourish the kidneys and liver, and soothe miscarriages. Moreover, there is evidence that DZ is capable of regulating blood pressure (BP), and several compounds isolated from DZ have been shown to have a BP-lowering effect. Quanduzhong capsules contain an extract of DZ [Eucommia ulmoides Oliv. (Eucommiaceae; Eucommiae cortex)] that is effective in treating hypertension. This multicenter, randomized, double-blind, placebo-controlled clinical trial sought to evaluate the clinical efficacy of Quanduzhong capsules in the treatment of low-to-moderate risk grade 1 hypertension patients. Materials and methods: A total of 60 patients from 3 centers with documented low-to-moderate risk grade 1 hypertension were randomly assigned in a 1:1 ratio to the test group or the control group. After a 1 week lead-in period using sham Quanduzhong capsules, all patients who met the entry criteria (29 cases in the test group and 29 cases in the control group) entered the 4 week test period. The test group took Quanduzhong capsules, and the control group continued to take sham Quanduzhong capsules. The primary endpoints [24-h mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) determined via 24-h ambulatory blood pressure monitoring (ABPM); office SBP and DBP] and secondary endpoints [mean arterial pressure; mean pulse; daytime mean SBP and DBP; nocturnal mean SBP and DBP; SBP and DBP load; area under the blood pressure (BP) curve; morning peak BP; early morning SBP and DBP; smoothness index of SBP and DBP; 24 h BP mean coefficient of variation (CV); percentage of patients with circadian restoration in ABPM; home BP; quality of life evaluated by WHO Quality of Life-BREF questionnaire; grading and quantitative evaluation of hypertension symptoms; values of plasmatic renin activity, angiotensin II, aldosterone, β-2 microglobulin and homocysteine] were assessed following the treatment. Drug-related adverse events and adverse drug reactions were also compared. Results: After a 4 week test period, a significant difference in the DBP CV between the two groups was observed (−2.49 ± 4.32 vs. 0.76 ± 4.3; p < .05). Moreover, the mean office SBP change was −7.62 ± 9.32 mmHg, and the mean DBP change was −4.66 ± 6.03 (p < .05). Among the three subjects with abnormal homocysteine levels in the test group, homocysteine levels decreased by 6.23 ± 9.15 μmol/L after treatment. No differences were observed between the two groups in any other indicators. After 4 weeks of treatment, there were no significant differences between the groups in terms of safety indicators (p > .05). No abnormal vital signs (except BP) or severe liver or renal function impairment were observed during the treatment periods; in addition, adverse events and drug reactions were mild. Conclusion: Treatment with Quanduzhong capsules reduced office SBP and DBP as well as DBP CV determined by 24-h ambulatory BP monitoring in patients with grade 1 hypertension at low-to-moderate risk. Clinical Trial Registration:https://www.chictr.org.cn/showproj.aspx?proj=32531, identifier ChiCTR1900021699.